Self‐collected vaginal specimens for human papillomavirus testing and guidance on screening exit: An update to the American Cancer Society cervical cancer screening guideline - Rebecca B. Perkins; Andrew M. D. Wolf; Timothy R. Church; Elena B. Elkin; Steven J. Skates; Ruth D. Etzioni; Carmen E. Guerra; Abbe Herzig; Richard M. Hoffman; Kevin C. Oeffinger; Sana Raoof; Ya‐Chen Tina Shih; et al. (CA: A Cancer Journal for Clinicians, 2026)
Abstract This update expands the 2020 American Cancer Society (ACS) cervical cancer screening guideline for average‐risk women and individuals with a cervix who are at average risk, to include self‐collection for human papillomavirus (HPV) testing and revised guidance for exiting cervical cancer screening. Self‐collected vaginal specimens, a method of primary HPV testing, align with the ACS cervical cancer screening guideline. When clinician‐collected cervical specimens are used for HPV testing, repeat screening is recommended every 5 years for those with a negative test. For self‐collected vaginal specimens, the ACS endorses the following recommendations of the Enduring Consensus Cervical Cancer Screening and Management Guidelines Committee (of which it is a member): (1) primary HPV screening using clinician‐collected cervical specimens is preferred, and self‐collected vaginal specimens are acceptable for average‐risk individuals aged 25–65 years; and (2) repeat testing in 3 years is recommended after a negative result on a self‐collected HPV screening test. These recommendations apply only to combinations of collection devices and HPV assays approved by the US Food and Drug Administration for HPV testing in a clinical setting or at home. The rationale notes that the use of self‐collected vaginal specimens can overcome barriers to screening for many patients, but most patients who test HPV‐positive will require extra follow‐up steps, and data on long‐term, real‐world effectiveness are limited. For certain high‐risk individuals, clinician‐collected samples are still recommended. Furthermore, in response to high rates of cervical cancer among individuals older than 65 years and with poor implementation of current exiting screening criteria, ACS has amended the 2020 guideline to recommend HPV testing at ages 60 and 65 years, with the last HPV test at an age no younger than 65 years as a requisite to exiting screening. The revised recommendation states: To qualify for discontinuation of screening, the ACS recommends an average‐risk woman or an individual with a cervix at average risk have negative primary HPV tests (preferred) or negative co‐testing using HPV tests and cytology (acceptable) at ages 60 and 65 years. If primary HPV tests or co‐testing are not available, three consecutive negative cytology (Papanicolaou) tests at the recommended screening interval with the last test at age 65 years are acceptable. If self‐collected vaginal specimens are used for HPV testing, the 3‐year testing interval should be followed. Additional screening exit stipulations relate to women at higher risk because of prior abnormal test results or current immune suppression.